K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 10 2021

\(\left(2x-1\right)\left(x+2\right)-\left(x-3\right)\left(x+3\right)\)

\(=2x^2+3x-2-x^2+9\)

\(=x^2+3x+7\)

23 tháng 8 2021

\(\left(x-2\right)^3+\left(2x+1\right)^2+2\left(x+2\right)\left(1-x\right)-9x^3+2x\)

\(=x^3-6x^2+12x-8+8x^3+12x^2+6x+1+2\left(x+2\right)\left(1-x\right)-9x^3+2x\)

\(=9x^3+6x^2+18x-7+2\left(x-x^2+2-2x\right)-9x^3+2x\)

\(=6x^2+20x-7-2x^2-2x+4=4x^2+18x-3\)

23 tháng 8 2021

Trả lời:

( x - 2 )3 + ( 2x + 1 )3 + 2 ( x + 2 )( 1 - x ) - 9x3 + 2x

= x3 - 6x2 + 12x - 8 + 8x3 + 12x2 + 6x + 1 + 2 ( x - x2 + 2 - 2x ) - 9x3 + 2x 

= 9x3 + 6x2 + 18x - 7 + 2x - 2x2 + 4 - 4x - 9x3 + 2x 

= 4x2 + 18x - 3 

22 tháng 2 2022

`Answer:`

`a)`

`A=5(x+1)^2-3(x-3)^2-4(x^2-4)`

`=>A=5(x^2+2x+1)-3(x^2-6x+9)-4x^2+16`

`=>A=5x^2+10x+5-3x^2+18x-27-4x^2+16`

`=>A=(5x^2-3x^2-4x^2)+(10x+18x)+(5-27+16)`

`=>A=-2x^2+28x-6`

`b)`

`B=5(x+1)^2-3(x-3)^2-4(x+2)(x-2)`

`=2x(3x+5)-3(3x+5)-2x(x^2-4x+4)-[(2x)^2-3^2]`

`=6x^2+10x-9x-15-2x^3+8x^2-8x-4x^2+9`

`=(6x^2-4x^2+8x^2)-2x^3+(10x-9x-8x)+(-15+9)`

Thay `x=-7` vào ta được:

`B=10(-7)^2-2(-7)^3-7(-7)-6`

`=>B=10.49-2(-343)+49-6`

`=>B=490+686+49-6`

`=>B=1219`

21 tháng 6 2017

 2x(2x-1)^2-3x(x+3)(x-3)+4x(x-1) 

2x(4x^2 - 4x + 1) - 3x(x^2 - 9) + 4x^2 - 4x 

= 8x^3 - 8x^2 + 2x - 3x^3 + 27x + 4x^2 - 4x 

= (8x^3 - 3x^3) + (-8x^2+ 4x^2) + (2x +27x - 4x) 

= 5x^3 - 4x^2 + 25x 

= x(5x^2 - 4x + 25)

Vậy........

18 tháng 12 2021

Answer:

\(\left(2x+1\right)^2+\left(2x-1\right)^2-2\left(1+2x\right)\left(2x-1\right)\)

\(=(4x^2+4x+1)+(4x^2-4x+1)-2(4x^2-1)\)

\(=4x^2+4x+1+4x^2-4x+1-8x^2+2\)

\(=(4x^2+4x^2-8x^2)+(4x-4x)+(1+1+2)\)

\(=4\)

\((x-1)^3-(x+2)(x^2-2x+4)+3(x-1)(x+1)\)

\(=(x^3-3x^2+3x-1)-(x^3+8)+3(x^2-1)\)

\(=x^3-3x^2+3x-1-x^3-8+3x^2-3\)

\(=(x^3-x^3)+(-3x^2+3x^2)+3x+(-1-8-3)\)

\(=3x-12\)

3 tháng 12 2016

Đặt \(A=\frac{2x^3+x^2-2x+1}{x^3+2x^2-x-2}\)

        \(A=\frac{x^2.\left(2x+1\right)-2x-1+2}{x^3+x^2+x^2+x-2x-2}\)

        \(A=\frac{x^2\left(2x+1\right)-\left(2x+1\right)+2}{\left(x^2+x-2\right)\left(x+1\right)}\)

       \(A=\frac{\left(x^2-1\right)\left(2x+1\right)+2}{\left(x+2\right)\left(x-1\right)\left(x+1\right)}\)

       \(A=\frac{\left(x-1\right)\left(x+1\right)\left(2x+1\right)+2}{\left(x-1\right)\left(x+1\right)\left(2x+1\right)}\)

       \(A=1+\frac{2}{\left(x-1\right)\left(x+1\right)\left(2x+1\right)}\)